PENGARUH KEBANGGAAN TERHADAP ORGANISASI, GAYA KEPEMIMPINAN DAN KOMITMEN, TERHADAP KINERJA PEGAWAI - Sujartono Hasyim; Samdin Samdin; Noval Nur (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objective of this research is to examine and explain the effect of organizational based self esteem, leadership style, commitment to employees performance of the South Mowila Konawe Regency.  The approach of this research is survey method with explanatory research design.  Data was collected with an instrument in the form of questionnaires.  The population of the research was 39 employees of the Mowila Head Office.  The analytical tool used to test the hypothesis was multiple linear regression.  The result showed that organizational based self esteem, leadership, and commitment simultaneously had significant effect on employees performance.  Organizational based self esteem and commitment partially have significant effect on employees performance, while leadership style had positive but insignificant effect on employees performance.  Finally, this research shows that leadership style does not have partial effect on employees performance, but can prove that organizational based self esteem, leadership style, and commitment affected the performance of Mowila district office employees.Keywords: organizational based self esteem, leadership style, commitment and employees performance